Análise crítica no processo de outorga no Estado do Ceará: estudo de caso no Vale do Rio Curu - Araújo, Adriana Débora Chagas de (2014)
This paper presents a proposal for the grant application as a management tool in the allocation to the valley of Curu river in the state of Ceará. Were developed and presented historical series of simulations of reservoirs, as well as assumptions of using the grant as a tool for allocation, based on water demands of the Curu river valley. Were estimated by registering the demands of users conducted by COGERH in 2013 and the record of the grants awarded in the same year. Simulations with Sagreh and ACQUANET programs for the following year, including an estimate of growth in the region that still has a number of large areas into disuse were also made. Observing the variables found a study on the risk of not meeting the demands, based on historical series of scarcity and reduction of flow was made. This study applied if the demands: estimated, granted and maximum theoretically and tested a strategy for the grant application as a management tool to be considered in the allocation to systematize the use of water in the basin and the river valley Curu.